Body mass index was linked with multi-cardiometabolic abnormalities in Chinese children and adolescents: a community-based survey - Huijing He; Li Pan; Jianwei Du; Yuming Jin; Pengben Jia; Guangliang Shan (BMC, 2022)
Abstract Background Evidence on how body mass index (BMI) influence cardiometabolic health remains sparse in Chinese children and adolescents, especially in south China. We aim to investigate the effect of overweight and/or obesity on high blood pressure (HBP), dyslipidemia, elevated serum uric acid (SUA) and their clustering among children and adolescents in an island in South China. Methods Using multi-stage cluster sampling method, 1577 children and adolescents aged 7-18 in Hainan province, south China, participated in the survey. The association between body mass index and cardiometabolic indexes were explored. Overweight and obesity were classified according to criteria of World Health Organization for children and adolescents aged 5 to 19. Restricted cubic spline models were used to examine the possible non-linear association between BMI and cardiometabolic profiles. Multivariable logistic regression models were fitted to examine the effect size of BMI on cardiometabolic disorders including HBP, elevated SUA and dyslipidemia. Comorbidity of at least two cardiometabolic abnormalities (HBP, dyslipidemia, elevated SUA) was defined as clustering of cardiometabolic risk factors. Results Comparing with normal weight and underweight subjects, overweight/obese youths had higher levels of BP, SUA, triglyceride, low-density lipoprotein but lower level of high-density lipoprotein. Overweight/obese youth had higher risk of dyslipidemia (OR:2.89, 95%CI: 1.65-5.06), HBP (OR:2.813, 95%CI: 1.20-6.59) and elevated SUA (OR: 2.493, 95%CI: 1.45-4.27), respectively, than their counterparts. The sex-, age-adjusted prevalence of abnormalities clustering was 32.61% (95% CI: 20.95% to 46.92%) in overweight/obesity group, much higher than in the under/normal weight group (8.85%, 95%CI: 7.44% to 10.48%). Conclusion Excess adiposity increased the risk of elevated serum uric acid, serum lipids, blood pressure and their clustering among children and adolescents in south China.